2018
DOI: 10.1021/acscatal.8b02274
|View full text |Cite
|
Sign up to set email alerts
|

Deconvoluting the Competing Effects of Zeolite Framework Topology and Diffusion Path Length on Methanol to Hydrocarbons Reaction

Abstract: Micropore topology and crystal size are two independently adjustable properties that govern the internal mass transport limitations of zeolite catalysts. Deciphering the relative impact of each factor on catalyst performance is often nontrivial owing to the inability to synthesize zeolites with predetermined physicochemical properties. In this study, a series of ZSM-11 (MEL) and ZSM-5 (MFI) catalysts of equivalent acidity, but differing pore architecture, are prepared with well-defined crystal sizes to elucida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 49 publications
5
60
0
Order By: Relevance
“…The preferential orientations of the thin films were examined by X‐ray diffraction (XRD, Figure e) . Operando UV/Vis diffuse reflectance spectroscopy (DRS) coupled with on‐line MS was used to investigate the MTH process over the oriented zeolite ZSM‐5 thin films . The results (Figures a,b and S3) reveal distinct UV/Vis absorption of hydrocarbon species in the two oriented thin films, illustrating different coking behaviors.…”
Section: Figurementioning
confidence: 99%
“…The preferential orientations of the thin films were examined by X‐ray diffraction (XRD, Figure e) . Operando UV/Vis diffuse reflectance spectroscopy (DRS) coupled with on‐line MS was used to investigate the MTH process over the oriented zeolite ZSM‐5 thin films . The results (Figures a,b and S3) reveal distinct UV/Vis absorption of hydrocarbon species in the two oriented thin films, illustrating different coking behaviors.…”
Section: Figurementioning
confidence: 99%
“…Despite its industrial significance 30 , 31 , MTO over zeolite catalysts is a complicated process controlled by sophisticated reaction network and molecular diffusion 32 34 . Carbonaceous species are deposited in the catalyst crystals, leading to the induction, autocatalysis and rapid deactivation.…”
Section: Introductionmentioning
confidence: 99%
“…Reports centered around the topological features and their relevance in catalysis have shown that zeolites with relatively small pores, specifically 10-membered channels, have better selectivity toward light olefins [25]. Relatively larger pore zeolites, such as MOR and Beta, are popular in reactions involving the aromatization of olefins, although they tend to deactivate easily and they also require comparatively higher concentrations of substrates [26][27][28]. Hence, the pore dimension and framework features are crucial for the conversion process and product selectivity.…”
Section: Introductionmentioning
confidence: 99%